2018
DOI: 10.1007/s13105-018-0620-6
|View full text |Cite
|
Sign up to set email alerts
|

Sceletium tortuosum may delay chronic disease progression via alkaloid-dependent antioxidant or anti-inflammatory action

Abstract: The link between obesity-induced systemic inflammation and decreased insulin signalling is well-known. It is also known that peripherally produced inflammatory cytokines can cross the blood-brain barrier, resulting in the release of neurotoxins that can ultimately lead to the demise of central nervous system integrity. A high-mesembrine Sceletium tortuosum extract was recently shown to possess cytoprotective and mild anti-inflammatory properties in monocytes and to target specific p450 enzymes to reduce adrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Moreover, this process serves the prevention of further spreading to the rest of the body as protection [ 74 ]. Bennett and colleagues [ 13 ] reported that the cytokine was associated with inflammatory stimulus.…”
Section: Biological and Pharmaceutical Properties Of Sceletium Spmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, this process serves the prevention of further spreading to the rest of the body as protection [ 74 ]. Bennett and colleagues [ 13 ] reported that the cytokine was associated with inflammatory stimulus.…”
Section: Biological and Pharmaceutical Properties Of Sceletium Spmentioning
confidence: 99%
“…Hence, cytokine response affected the interleukin-6 (IL-6) and monocyte chemotactic protein-1 (MCP-1), with p < 0.005 and p < 0.0005, respectively. The results showed high concentrations of mesembrine Sceletium extracts, demonstrating anti-inflammatory properties [ 13 ]. In vivo studies, male Wistar rats were administered S. tortuosum extracts.…”
Section: Biological and Pharmaceutical Properties Of Sceletium Spmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesembrine serves a primary function as a monoamine releasing agent (MRA) and secondly as a selective serotonin reuptake inhibitor (SSRI), drug classes most commonly utilized in the treatment of anxiety and depression [23,24]. Another alkaloid found in S. tortuosum is delta 7 mesembrenone, it is a potent antioxidant, and a powerful inhibitor of tyrosinase activity, kojic acid at high doses had an almost identical effect on this enzyme [25]. Alkaloid composition in different S. tortuosum plant extracts vary, and higher concentrations of certain alkaloids can have different medical properties.…”
Section: Introductionmentioning
confidence: 99%